Wi-Fi Direct Research ‐ Current Status and Future Perspectives. (1st September 2017) - Khan, Muhammad Asif; Cherif, Wael; Filali, Fethi; Hamila, Ridha
Abstract: Wi-Fi Direct, also named Wi-Fi P2P, is a popular technology that enables device to device communication in Wireless LAN. It allows Wi-Fi Direct-enabled devices to dynamically negotiate and select one of the mobile devices as Group Owner. The Group Owner plays the role of an Access Point as in Wi-Fi infrastructure mode. Wi-Fi Direct protocol was initially released to connect Wi-Fi enabled devices on the fly. However, due to the enhanced features, the protocol has the potential to be used in several applications such as files transferring, sharing resources, online gaming, alert dissemination, social networking, etc. An extensive survey on Wi-Fi Direct technology and a review of state-of-the-art is presented in this paper. An insight into current research works, applications, and challenges related to Wi-Fi Direct is provided. Moreover, the paper presents our proposed Group Formation scheme, which aims to enhance the performance of Wi-Fi Direct networks.